1997
DOI: 10.1111/j.1744-6570.1997.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Rater‐ratee Race Effects in Developmental Performance Ratings of Managers

Abstract: The effects of rater and ratee race on performance ratings of managers were examined. Ratings were obtained from peers, subordinates and bosses as part of a multirater, developmental feedback program for managers. Two data sets were created for purposes of this study. The between‐subjects data set consisted of ratings from over 20,000 bosses, over 50,000 peers, and over 40,000 subordinates. The repeated measures data set was substantially smaller because it included only those Black and White managers who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 29 publications
8
40
1
Order By: Relevance
“…In general, subsequent examinations of race have also reported rater-ratee similarity effects, with the bulk of studies examining Black and White groups (Biernat et al, 1998;Elvira & Town, 2001;Kraiger & Ford, 1985;Mount et al, 1997;Stauffer & Buckley, 2005). Tsui and O'Reilly (1989) found no evidence for race (Black-White) dissimilarity effects on performance ratings, but Tsui et al (2002) reported that race dissimilarity affected ratings of extrarole performance.…”
Section: Dyadic Similaritymentioning
confidence: 92%
See 2 more Smart Citations
“…In general, subsequent examinations of race have also reported rater-ratee similarity effects, with the bulk of studies examining Black and White groups (Biernat et al, 1998;Elvira & Town, 2001;Kraiger & Ford, 1985;Mount et al, 1997;Stauffer & Buckley, 2005). Tsui and O'Reilly (1989) found no evidence for race (Black-White) dissimilarity effects on performance ratings, but Tsui et al (2002) reported that race dissimilarity affected ratings of extrarole performance.…”
Section: Dyadic Similaritymentioning
confidence: 92%
“…Several studies suggest a greater negative effect of racial dissimilarity on ratings made by White evaluators. In Mount et al (1997), both Black and White superiors assigned more favorable ratings to same race ratees, with the greatest difference between raters for Black ratees. Stauffer and Buckley (2005) found that higher ratings were given to White ratees by both White and Black supervisors.…”
Section: Dyadic Similaritymentioning
confidence: 94%
See 1 more Smart Citation
“…Dubey (1970) found that African Americans are generally "indifferent to the race" of those holding leadership roles in business or religious organizations. A large study of black and white managers, subordinates and peers found that black subordinates rated black bosses more highly than they rated white bosses; however the same effect was not true for whites: white subordinates did not differ in their ratings of white and black bosses (Mount, Sytsma, Hazucha, & Holt, 1997). Recent lab studies also suggest that same-group membership is not as predictive as one might think.…”
Section: Explaining the Constraints Of Race-ethnicitymentioning
confidence: 93%
“…who also simulated a rape case, reported that guilty verdicts were significantly more likely when the victim was of the same race as the juror than when the two were of different races. Preferential treatment for members of one's own race was also demonstrated when the dependent variable was the performance rating of an employee (Kraiger & Ford, 1985;Mount, Sytsma, Hazucha, & Holt, 1997).…”
mentioning
confidence: 98%